The Role of Albumin-To-Fibrinogen and Fibrinogen-To-Prealbumin Ratios in the Development of Ovarian Carcinoma - Racheva V.; Dekova I.; Gorcheva Z.; Semova T.; Dimitrov D.; Petkova E. (Acta Medica Bulgarica, 2025)
Ovarian carcinoma (OC) has the highest mortality among gynecological carcinomas in developed countries. Many authors have drawn attention to fibrinogen-to-pre-albumin (FPR) and albumin-to-fibrinogen (AFR) ratios and demonstrated that low AFR values and high FPR values correlate with an increased risk of mortality and recurrence of carcinoma and may be promising prognostic markers for malignant diseases. As emerging biomarkers, FPR and AFR have significant advantages due to their availability, costeffectiveness, and reliability.